(untitled) (Psychology Travelogs, 2024)
The article presents the results of psychophysiological studies of the professional suitability of job candidates. The experimental data obtained indicate the high efficiency of the joint use of IT-examination and polygraph. The conducted research confirms the prospects of using itracking to reveal hidden information in the organisation of professional personnel selection. The research has shown that the method of assessing the psycho-emotional state of a person based on video oculography allows recording psycho-emotional and psychophysiological reactions of a person to identify hidden information without connecting multiple sensors, with a coincidence of 80% between the data obtained on a polygraph and an ITracker. The most informative parameters of evoked brain activity are the zones in the interval of 250-550 ms. In this zone of evoked potentials, there are significant differences between the amplitudes of evoked potentials of individuals with and without drug use experience. The peculiarity of the differences found is that the amplitude of the P300 wave of individuals who did not use drugs exceeds the amplitude of the same wave of individuals who used drugs. The results of the analysis using a computer program of evoked brain potentials during the presentation of drug-related slides can be used to determine the social and psychological reliability of job candidates. Those who have changes in the assessment of the affective intensity of the information presented, associated with repeated use of soft drugs, are considered professionally unfit.